Optimalisasi Peran Panglima Laot Terhadap Ketertiban Wilayah Pesisir di Aceh - Jalaluddin Jalaluddin; Budi Handoyo; Anhar Fazri; Mukhlizar Mukhlizar (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2023)
Panglima Laot in Qanun number 10 of 2008 concerning Customary Institutions in Aceh. Laot in Acehnese grammar means sea and Panglima itself means Leader. Panglima Laot in this case is part of the customary institutions in Aceh as a special region that has a distinctive regional implementation. Panglima Laot has existed since the reign of Sultan Iskandar Muda, who had a vital role in leading the army of his time. Citing this name, Panglima Laot today is more directed to the function of maintaining maritime order through upholding traditional values that are still believed by the fishing community in Aceh. However, the role of Panglima Laot is degraded by the functions and powers of law enforcement officials who have a more optimal role in carrying out this role. So it is important to study how to optimize Panglima Laot in the order of the Aceh coastal area. The research method used is sociological juridical or empirical juridical. Panglima Laot's urgency in building order among coastal communities in Aceh is reflected in the Regional Regulations which accommodate the role and function of the Panglima to always be involved in law enforcement, especially according to custom in Aceh. For this reason, optimizing the role of Panglima Laot can be carried out by placing capable human resources in exercising authority in that position, both in communication, public administration skills and also being trusted as individuals capable of upholding customary law by the people of the Aceh region.